PENGATURAN/FORMULASI PIDANA MATI TERHADAP TINDAK PIDANA KORUPSI DI CHINA, VIETNAM, DAN THAILAND - Irvino Rangkuti (Faculty of Law, Maranatha Christian University, 2023)
The purpose of this study is to clarify the application of the death penalty against corruptors in other countries and to assess existing laws in Indonesia whether the death penalty is used against corruptors and causes conflict. The death penalty is classified as an extraordinary crime. This study uses research that uses prescriptive legal methods. This research is descriptive in nature. The analysis technique used is descriptive technique and the collection of legal material used is literature search. This study uses a statutory approach to evaluate existing regulations. The production of this journal is based on a comparative approach. This approach is carried out as a comparison of existing regulations in Indonesia with regulations in other countries. The conclusion from writing this diary is that there are differences in the rules for applying the death penalty for corruptors in Vietnam and in Thailand, where there is a degree of corruption that makes the death penalty a threat. On the other hand, in Indonesia, corrupt people can be executed because there is no fixed level of income from corruption. Another thing that affects the application of the death penalty in Indonesia is that Indonesia has regulations that conflict with the death penalty.